Necitumumab plus gemcitabine and cisplatin as first-line therapy in patients with stage IV EGFR- expressing squamous non-small-cell lung cancer: German subgroup data from an open-label, randomized controlled phase 3 study (SQUIRE) - Reck, Martin; Thomas, Michael (Oncology research and treatment, 2016)
Background: In the SQUIRE study, adding the anti-epidermal growth factor receptor (EGFR) IgG1 antibody necitumumab to first-line gemcitabine and cisplatin (GC + N